La aplicación de las técnicas grafo-plásticas para mejorar el desarrollo de la motricidad fina en niños y niñas de 4 a 5 años de edad de la escuela fiscal Ciudad de Loja, período 2014-2015 - Mendoza Solano, Silvana Elizabeth (2016)
The following research is called: A THE APPLICATION OF GRAPHO-PLASTIC TECHNIQUES FOR IMPROVING THE FINE MOTILITY DEVELOPMENT IN 4 TO 5 YEAR OLD KINDS OF THE CIUDAD DE LOJA, PERIOD 2014-2015, for which the following general objective has been set down: determine public-school the importance the grapho-plastic techniques have in the improvement of the fine motility development in 4to 5 year old kids of the Ciudad de Loja public school, period 2014-2015; the use of grapho-plastic techniques is the only way to reach the previously mentioned, therefore the methodology is of a descriptive and correlational type, the methods that were used in present research are: the inductive-deductive, analytical- synthetical, descriptive; as to the techniques used for this work we have the interview; and, as tool, the GoodardDexterímetro test applied to 4-5 year old kids, the procedure the present investigation was at institutional level, which, with the Ciudad de Loja public school´s Director, the “A” class, and the Kids permission to carry out the field out the field investigation, with a population of 26 kids and 3 teachers; after doing the analysis of the results we obtained, it is concluded that the grapho-plastics techniques are important in the improvement of the improvement of the fine motor development, they help correct the preciseness and coordination un 4to 5 year old kids